2019
DOI: 10.3390/s19122824
|View full text |Cite
|
Sign up to set email alerts
|

Facile Non-Enzymatic Electrochemical Sensing for Glucose Based on Cu2O–BSA Nanoparticles Modified GCE

Abstract: Transition-metal nanomaterials are very important to non-enzymatic glucose sensing because of their excellent electrocatalytic ability, good selectivity, the fact that they are not easily interfered with by chloride ion (Cl−), and low cost. However, the linear detection range needs to be expanded. In this paper, Cu2O–bovine serum albumin (BSA) core-shell nanoparticles (NPs) were synthesized for the first time in air at room temperature by a facile and green route. The structure and morphology of Cu2O–BSA NPs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 74 publications
1
16
0
Order By: Relevance
“…Additionally, an insignificant redox peak appears in the absence of BPA, which could be attributed to formation of electroactive species (NiOOH/CuOOH) in alkaline media and in accordance with the reported literature . Herein, we selected alkaline media because it supports the fast and easy formation of electroactive species and provides high stability to BPA …”
Section: Resultssupporting
confidence: 80%
“…Additionally, an insignificant redox peak appears in the absence of BPA, which could be attributed to formation of electroactive species (NiOOH/CuOOH) in alkaline media and in accordance with the reported literature . Herein, we selected alkaline media because it supports the fast and easy formation of electroactive species and provides high stability to BPA …”
Section: Resultssupporting
confidence: 80%
“…Despite their promising results, none of them has been fully successful for use by the general population, since they do not provide a direct glycemia measurement [10]. CGM based upon electrochemical means are also being studied [11,12,13,14,15,16], but the continuous need of disposable stuff and the errors they present [17] (mainly because of the inflammation of the skin in the surroundings of the sensor placing) suggest that alternative solutions should be explored [18,19]. Some other methods have been investigated, such as trying to measure glycemia from the individual’s breath [20,21], saliva [22], tears [23,24], or gingival crevicular fluid [25], although conclusive results have not been found yet.…”
Section: Introductionmentioning
confidence: 99%
“…Glucose (D-(+) glucose, Sigma Aldrich, Missouri, USA) in 0.1 M NaOH was used to determine the EC sensing capability of the graphene/Ni hybrid mesh electrodes. It has been reported that the current of CVs increase with the pH value of the electrolyte [ 37 ]. Since the 0.1 M NaOH solution could yield a high pH value of 13, we chose it as the electrolyte to promote the currents of CVs.…”
Section: Methodsmentioning
confidence: 99%